OVERVIEW OF HYDROMETALLURGICAL METHODS FOR PROCESSING ZINC-CONTAINING TECHNOGENIC WASTE - Ismailov Jonibek Baxadirovich (Journal Park Publishing, 2025)
This review examines various hydrometallurgical strategies for recovering valuable metals from zinc-containing industrial wastes, such as basic oxygen steelmaking (BOS) filter cakes, hot filter cakes (HFC), and zinc plant residues. The study analyzes different leaching agents, including organic acids (butyric, citric), inorganic acids (sulfuric, hydrochloric), and complexing agents (thiosulfate, thiourea). Key findings indicate that zinc recovery rates can reach up to 84.6% using selective organic leaching, while associated metals like cobalt, manganese, lead, and silver show recovery efficiencies exceeding 90% under optimized conditions. This paper provides a comparative analysis of recovery rates, selectivity, and methodological advantages to support sustainable metallurgical waste management.
Keywords: BOS filter cakes, hot filter cake (HFC), hydrometallurgy, selective leaching, reductive leaching, zinc recovery, silver recovery, cobalt, manganese, butyric acid, citric acid, thiosulfate, chloride solutions.